Cestodes in Eurasian wolves (Canis lupus lupus) and domestic dogs (Canis lupus familiaris) in Switzerland - Anna Schneider; Gastón Moré; Mirjam Pewsner; Caroline F. Frey; Walter Basso (International Journal for Parasitology: Parasites and Wildlife)
Eurasian wolves (Canis lupus lupus) and domestic dogs (Canis lupus familiaris) are definitive hosts of numerous cestode species. While infections with adult stages in canids are usually subclinical, some species pose a zoonotic risk or cause infections in wildlife and livestock, resulting in disease and/or economic losses. This study aimed to determine the prevalence, species composition, and geographical distribution of cestode infections in dogs and free-ranging wolves in Switzerland. Faecal samples from 2065 dogs and intestinal content from 121 necropsied wolves were macroscopically examined and tested using zinc chloride flotation method. When cestode eggs or adult cestodes were detected, a molecular identification based on multiplex-PCR and sequencing was performed. In the sampled wolves, the prevalence by flotation (42/121; 34.7%) was lower than the overall prevalence including macroscopic examination (76/121; 62.8%). The flotation method thus failed to detect cestode infections in 44.7% (34/76) of infected wolves. The most frequently detected species was Taenia hydatigena (46/121; 38.0%), followed by Taenia serialis (23/121; 19.0%), Mesocestoides spp. (3/121; 2.5%), Taenia ovis (1/121; 0.8%), and Echinococcus multilocularis (1/121; 0.8%). In the analysed dogs, the prevalence was 0.9% (19/2065), but the real prevalence is very likely to be higher, as no necropsy data were available. Identified cestode species included Taenia crassiceps (6/2065; 0.3%), E. multilocularis (3/2065; 0.1%), Mesocestoides sp. (2/2065; 0.1%), Taenia polyacantha (1/2065; 0.05%), and Dibothriocephalus latus (1/2065; 0.05%). By identifying the cestode species infecting two closely related host species with markedly different lifestyles, this study sheds light on the local distribution of these parasites and their potential impacts on wildlife, livestock, and human health. Due to their close contact with humans, infected dogs represent an important source of infection with zoonotic cestodes such as Echinococcus spp. and certain Taenia species, responsible for serious human diseases.